2018 Vegetable Production Handbook Chapter 15: Root Crop Production - Peter J. Dittmar; Eugene J. McAvoy; Monica Ozores-Hampton; Richard Raid; Hugh A. Smith; Bonnie Wells; Julien Beuzelin; Johan Desaeger; Joseph W. Noling; Lincoln Zotarelli; Shouan Zhang; Christian F. Miller; et al. (EDIS)
This 35-page fact sheet is chapter 15 of the 2018 Vegetable Production Handbook. Written by Peter J. Dittmar, Eugene J. McAvoy, Monica Ozores-Hampton, Richard Raid, Hugh A. Smith, Bonnie Wells, Julien Beuzelin, Johan Desaeger, Joseph W. Noling, Lincoln Zotarelli, Shouan Zhang, Christian F. Miller, and Qingren Wang, and published by the Horticultural Sciences Department, 2018.